2009
DOI: 10.18433/j35c7z
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Drug Interactions Associated with Length of Stay and Cost of Hospitalization

Abstract: Purpose To evaluate the prevalence of drug-drug interactions (DDI) in hospitalized patients and to identify associated risk factors. Methods A retrospective cross-sectional analysis of prescription data and medical records from a public hospital in Brazil was conducted to identify potential DDI. Inappropriate drug combinations were identified and classified with a standard drug interaction source. Primary diagnoses were classified with Charlson Comorbidity Index (CCI). Sex, age, polypharmacy and length of stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
164
7
24

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(220 citation statements)
references
References 20 publications
17
164
7
24
Order By: Relevance
“…These findings were in accordance with other studies which showed that both variables were indeed two of the major, if not the most important, risk factors for DDIs [6,14,[27][28][29]. Other risk factors for the occurrence of DDIs identified by other studies included sex [27] and length of hospital stay [4,6]. Although the current findings showed that DDIs were not preventable, awareness of the medical team on the prevalence, risk factors and mechanisms involved in the occurrence of potential DDIs can help in the reduction of the real occurrence of DDIs among hospitalized patients in general and the critically ill patients in specific.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were in accordance with other studies which showed that both variables were indeed two of the major, if not the most important, risk factors for DDIs [6,14,[27][28][29]. Other risk factors for the occurrence of DDIs identified by other studies included sex [27] and length of hospital stay [4,6]. Although the current findings showed that DDIs were not preventable, awareness of the medical team on the prevalence, risk factors and mechanisms involved in the occurrence of potential DDIs can help in the reduction of the real occurrence of DDIs among hospitalized patients in general and the critically ill patients in specific.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were comparable with those reportd in several studies [4][5][6]13,14,28,31]. Logistic regression analysis for the possible risk factors of DDIs among patients admitted to the CCUs in the present work showed that the age of patient and the number of prescribed drugs were the only significant factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Prevalence of potential DDIs (pDDIs) in hospital settings has been estimated in some recent studies to be in the range of 27.8 to 51.4 % [2][3][4]. Old age, taking increased number of medications, long hospital stay, gender and comorbid conditions have been reported as common risk factors for DDIs [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conducted at different part of the globe [12][13][14][15][16][17][18][19][20][21][22][23] showed that the prevalence of drug-drug interaction as well as its clinical significance (severity of interaction) varies from place to place depending on the presence of alternative drugs, variation in disease epidemiology and composition and level of health care professionals.…”
Section: Introductionmentioning
confidence: 99%